Survey Kondisi Fisik Pemain Futsal MA Nurul Islam Karancempaka Bluto Kabupaten Sumenep Madura - Lukman, Moh. Ardianto; Prasetyo, Dyas Andry; Mas’odi (SPRINTER: Jurnal Ilmu Olahraga, 2025)
Futsal is a sport that demands optimal physical fitness from its players. Physical fitness evaluation is fundamental in developing effective training programs, especially at the high school level. This study aims to determine the physical fitness profile of futsal players at MA Nurul Islam Karancempaka Bluto, Sumenep Regency, Madura, and provide appropriate training program recommendations.This study used a quantitative descriptive method with a cross-sectional design. The research subjects were 20 male futsal players from MA Nurul Islam Karancempaka aged 15-18 years. Parameters measured included anthropometry, aerobic capacity (Multistage Fitness Test), speed (30m sprint), agility (Illinois Agility Test), leg muscle strength (Vertical Jump), flexibility (Sit and Reach), and muscular endurance (Push-up and Sit-up). The results showed: (1) Average BMI 21.4 ± 2.1 kg/m² (normal category); (2) Average VO₂max 42.3 ± 4.8 ml/kg/min (moderate category); (3) Average 30m sprint speed 4.85 ± 0.32 seconds; (4) Average agility 16.2 ± 1.1 seconds; (5) Average vertical jump 45.3 ± 6.2 cm; (6) Average flexibility 28.7 ± 4.5 cm; (7) Average push-ups 32 ± 8 times; (8) Average sit-ups 35 ± 7 times. The physical fitness of MA Nurul Islam Karancempaka futsal players is in the moderate to good category. Special training programs are needed to improve aerobic capacity and sprint speed.